Reliability and construct validity of Maqasid Shariah knowledge questionnaire - Shalihin, Mohd Shaiful Ehsan; Hashi, Abdurezak Abdulahi; Che Ahmad, Aminudin; Musa, Ramli; Mohd Yusof, Nazri; Ahmad, Azmir; Mohamad Ismail, Mohamad Firdaus (UniKL Royal College of Medicine Perak (UniKL RCMP), 2024)
Maqaṣid Shariah is a holistic view of life with the concept of maintaining good conditions and ensuring the welfare of all humankind while preventing any harmful act, evil, or injury. In the context of medical practice, it shares similar objectives, particularly in promoting well-being and upholding principles of harm reduction. However, no local questionnaire or assessment tool currently available to measure the level of understanding of our community regarding Maqasid Shariah principles. Therefore, a newly developed, reliable, and valid questionnaire is needed. This study aimed to develop and validate a newly created questionnaire to assess knowledge of Maqasid Shariah. The questionnaire consists of 20 items, including a mix of true and false-choice questions and one best answer question on Maqasid Shariah topics. The questionnaire was distributed to 254 members of the medical community. Reliability was determined using Cronbach’s alpha for internal consistency, while construct validity was assessed using factor analysis. An acceptable degree of internal consistency was observed for the final 12 items (Cronbach’s alpha = 0.700). Factor analysis showed two meaningful components, which represent the background domain and the knowledge domain. This study indicates that this questionnaire is a reliable and valid tool for assessing the knowledge of respondents about Maqasid Shariah.